(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract The research’s goal lies in demonstrating the impact of the Federal Financial Supervision Endowment through the process of auditing the performance of the entities subject to its audit as to improve the performance of these entities, especially if the performance audit method is one of the newly applied methods that are compatible with the standards issued by the International Organization of Financial Supervision and Accounting Institutions which is the method of auditing performance according to the performance evaluation guide for programs and policies issued by the Federal Office of Financial Supervision. The research is based on a basic hypothesis that the contribution of the performance audit process according to the performance evaluation guide for programs and policies has an impact on improving the health insurance service provided by the company. The research has been concluded with a number of conclusions , the most important of which is the company’s need to keep pace with the Iraqi and Arabic Companies of Insurance and to extend its works fields as well as opening new spaces for new works including the realization of suitable works that contribute to flourish the company and to grow the national Economy via having the company issue medical insurances cards top the private sectors and to the citizens.